Profil Usaha Salon Kecantikan Tipe Pratama di Kota Padang - Emylda Marsendy; Rahmiati Rahmiati (JURNAL PENDIDIKAN DAN KELUARGA, 2020)
Padang. Salon is a profitable business, they consider that in the future the salon and beauty business is getting more advanced. Because now, the salon has become a basic need that must be met as a place of care and body beauty. This study aims to describe the profile of the beauty salon business in the city of Padang as seen from a) the quality of human resources (SDM), b) professional ethics of workers, c) the facilities and infrastructure used and d) the types of services provided. This type of research is quantitative descriptive. The population of this study was the leaders and workers of beauty salons registered at the P2T Office in Padang City which the total are 14 people and all were sampled (total sampling). Data collection technique was by using questionnaires adjusted in the form of Guttmann scale and Likert scale that have been tested for validity and reliability. Data analysis techniques use the percentage formula and categorization. Based on the results of the study note the level of achievement of respondents about the quality of human resources with the most TCR value is moderate and (71,42%), the level of achievement of respondents about professional ethics of employees with the most TCR value is moderate (76,67%), Level respondents' achievements about the type of service with the most TCR values ​​were very good (91,32%) and there were 6 equipment that could not be fully provided by all beauty salon types of Pratama in Padang City, there were 5 building standards that could not be fully owned by all beauty salons in Padang City and all good water standards that are fully owned by all beauty salons.This research is expected that the results of this study can be used as a source of information and input for the owner of Sali for the sake of the success of the salon in the future and be able to immediately correct any deficiencies in the salon so that the visiting respondents become satisfied and intend to return again at some time. Keywords: Pratama type salon, beauty salon busniess